1998
DOI: 10.1046/j.1365-2265.1998.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of bone mineral density and bone metabolism in transsexuals treated with cross‐sex hormones

Abstract: In M-->F, oestrogen treatment prevented bone loss after testosterone deprivation. In F-->M the testosterone dosage used, associated with a decline in serum oestradiol levels, was unable to maintain bone mass fully in all subjects in the longer term. The inverse relationship between BMD and serum LH levels suggests that the dose of hormone replacement has been too low in subjects with a decline in their BMD. Its cause might be underdosing or non-compliance in some patients. We propose that serum LH levels may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
5
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 31 publications
(22 reference statements)
8
117
5
1
Order By: Relevance
“…A rise in bone formation marker in trans men has been reported during the first 2 years of testosterone treatment (11,19) and higher bone formation markers were observed in trans men after long-term testosterone treatment vs control women (9). The latter long-term study also demonstrated higher serum levels of bone resorption markers, which is in agreement with the current results (9).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A rise in bone formation marker in trans men has been reported during the first 2 years of testosterone treatment (11,19) and higher bone formation markers were observed in trans men after long-term testosterone treatment vs control women (9). The latter long-term study also demonstrated higher serum levels of bone resorption markers, which is in agreement with the current results (9).…”
Section: Discussionsupporting
confidence: 82%
“…The latter long-term study also demonstrated higher serum levels of bone resorption markers, which is in agreement with the current results (9). However, not all studies in trans men documented higher bone resorption (11,19,20). Furthermore, our observations on areal bone parameters correspond with previous research reporting a preservation of aBMD during the first years of testosterone treatment (11,12,13,21,22) as well as after a longer exposure time and SRS (up to 10 years) in trans men (19,20,23).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A synergistic effect of Es on physical and emotional changes has been observed with these combinations (15,16). With regard to bone metabolism and the risk of developing osteoporosis, only two studies have been published, including 10 and 20 male-to-female transsexuals, respectively, with an observation period of more than one year (17,18). Antiandrogens were used in the reported treatment regimen to reduce T levels.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen administration in orchiectomized male-tofemale transsexuals showed an increase in BMD after 1 year of treatment, together with a reduction of the markers of bone turnover (50). Recently, high doses of estrogen have also been effective in male-to-female transsexuals when gonadotropin hormone-releasing hormone (GnRH) agonists were concomitantly used for the suppression of androgen production (51).…”
Section: Estradiol and Age-related Male Osteoporosismentioning
confidence: 99%